Electrochemical noise analysis of bioleaching of bornite (Cu5FeS4) by Acidithiobacillus ferrooxidans - Bevilaqua, D.; Acciari, H. A.; Benedetti, Assis Vicente [UNESP]; Fugivara, Cecilio Sadao [UNESP]; Tremiliosi Filho, G.; Garcia, O. (Elsevier B.V., 2006)
Electrochemical noise (EN) is a generic term describing the phenomenon of spontaneous fluctuations of potential or current noise of electrochemical systems. Since this technique provides a non-destructive condition for investigating corrosion processes, it can be useful to study the electrochemical oxidation of mineral sulfides by microorganisms, a process known as bacterial leaching of metals. This technique was utilized to investigate the dissolution of a bornite electrode in the absence (first 79 h) and after the addition of Acidithiobacillus ferrooxidans (next 113 h) in salts mineral medium at pH 1.8, without addition of the energy source (Fe2+ ions) for this chemolithotrophic bacterium. Potential and current noise data have been determined simultaneously with two identical working bornite electrodes which were linked by a zero resistance ammeter (ZRA). The mean potential, E-coup, coupling current, I-coup, standard deviations of potential and current noise fluctuations and noise resistance, R-n, have been obtained for coupled bornite electrodes. Noise measurements were recorded twice a day in an unstirred solution at 30 degrees C. Significant changes in these parameters were observed when the A. ferrooxidans suspension was added, related with bacterial activity on reduced species present in the sulfide moisture (Fe2+, S2-). ENA was a suitable tool for monitoring the changes of the corrosion behavior of bornite due to the presence of bacterium. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Acidithiobacillus ferrooxidans; bornite; bioleaching; electrochemical noise